Analisis Framing Media Tribun Jabar atas Strategi Komunikasi Dedi Mulyadi dalam Menangani Kenakalan Remaja melalui Program Barak Militer - Faris, Muhammad Adam; Fabrianus, Doni (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
Juvenile delinquency remains a growing social challenge in Indonesia, particularly in urban areas such as West Java. As a response, Dedi Mulyadi initiated a military-style boot camp program targeting troubled students, introducing a disciplinary and character-building approach through physical and mental training. This study aims to analyze how the local media, especially Tribun Jabar, frames Dedi Mulyadi’s communication strategy in addressing juvenile delinquency by applying Robert Entman’s framing theory. A qualitative content analysis was conducted on ten online news articles published in May 2025. The findings show that 80% of the news coverage positively frames the military boot camp program, emphasizing narratives of effectiveness, emotional resonance, and responsiveness attributed to Dedi Mulyadi’s leadership. Critical perspectives, such as those from the Indonesian Child Protection Commission (KPAI) and public intellectuals like Rocky Gerung, are included but are not given equal narrative weight. Entman’s four framing elements problem definition, causal diagnosis, moral judgment, and treatment recommendation are clearly manifested in the coverage, reinforcing a discourse that legitimizes the military-style solution as both necessary and moral. These media narratives significantly influence public perception and political imagery, reflecting a dominant framing that marginalizes alternative views on children's rights and the long-term efficacy of militaristic approaches.